KUALITAS ORGANOLEPTIK ABON AYAM YANG DIBERI PERLAKUAN SUBSTITUSI KACANG TANAH (Arachis hypogaea L.) - Miarsono Sigit; Mubarak Akbar; Lisa Fianti (Universitas Islam Kadiri, 2017)
The aims of this study was to determine the organoleptic quality of chicken abon who received different amounts of peanut substitution (Arachis hypogaelig L.). The study was done in the farm laboratory, Faculty of Agriculture, Kadiri Islamic University at 14-21 September 2014 Material used in this research was chicken abon who were given peanuts substitution treatment. Methods used in this research was the experiments method with Complete Random Design (RAL). Treatment of this research was the difference concentration of peanuts consisting of 4 treatment: K0: 250g chicken; K1: 225g chicken + 25g peanut = 8%; K2: 200g chicken + 50g peanuts = 16%; K3: 175g chicken + 75g peanuts = 24%; K4: 150g chicken + 100g peanuts = 32%. Organoleptic test of every panelist given a tray contains10 gr abon and water. Material assessed by the panelist presented to describe flavor, smell, color, and texture. The results of this research showed the addition of peanutsgive significant infuence (P<0.01) against odor, color and flavor of chicken abon.The average level of consumer’s preference test on odor start of the highest scores until lowest respectively is: F0 = 6.540; F1 = 6.328; F3 = 6.134; F2 = 6.100; F4= 5.994. The average level of consumer’s preference test on the color of the highest scores until lowest respectively was: F1 = 6.560; F0 = 6,500; F2 = 6.360; F4 = 6.260; F3 = 6.060. As for the average level of consumers preference test on the flavor of the highest scores until lowest respectively is: F0 = 6.606; F1 = 6.206; F3 = 6.146; F2 = 6,080; F4= 5.772. The addition of peanuts do not effect significantly (P>0.05) against texture of chicken abon. The average level of consumer’s preference from highest until lowest respectively is: F2 = 6.220; F3 = 6,200; F0 = 6.160; F1 = 6.040; F4 = 6,000 Based on this research done so it is recommended that the addition of peanuts to make chicken abon can be done by a dose of 8 % 90 to yielding an odor, color and flavor abon that favored by consumers.